2003
DOI: 10.1152/jn.00616.2003
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid Peptide Activates Non-α7 Nicotinic Acetylcholine Receptors in Rat Basal Forebrain Neurons

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative condition characterized by profound deficits in memory and cognitive function. Neuropathological hallmarks of the disease include a loss of basal forebrain cholinergic neurons and the deposition of beta-amyloid peptide (Abeta) in neuritic plaques. At a cellular level, considerable attention has focused on a study of Abeta interactions with the neuronal nicotinic acetylcholine receptor (nAChR) subtypes. In this study, using cell-attached and outside-ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 41 publications
(55 reference statements)
2
58
0
Order By: Relevance
“…A number of electrophysiological studies, in a variety of in vitro preparations, have demonstrated that A␤ 1-42 can exert its effects through both ␣7 and ␣4␤2 nAChRs (Pettit et al, 2001;Dineley et al, 2002;Fu and Jhamandas, 2003;Wu et al, 2004;Lamb et al, 2005). However, the precise nature of A␤ 1-42 interactions with nAChRs is controversial because some studies have reported that A␤ 1-42 activates nAChRs (Dineley et al, 2002;Fu and Jhamandas, 2003), whereas other studies suggested that A␤ 1-42 inhibits nAChRs (Pettit et al, 2001;Wu et al, 2004;Lamb et al, 2005). Both ␣7 and non-␣7 subtypes of nAChRs were reported to be involved in such A␤-mediated interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of electrophysiological studies, in a variety of in vitro preparations, have demonstrated that A␤ 1-42 can exert its effects through both ␣7 and ␣4␤2 nAChRs (Pettit et al, 2001;Dineley et al, 2002;Fu and Jhamandas, 2003;Wu et al, 2004;Lamb et al, 2005). However, the precise nature of A␤ 1-42 interactions with nAChRs is controversial because some studies have reported that A␤ 1-42 activates nAChRs (Dineley et al, 2002;Fu and Jhamandas, 2003), whereas other studies suggested that A␤ 1-42 inhibits nAChRs (Pettit et al, 2001;Wu et al, 2004;Lamb et al, 2005). Both ␣7 and non-␣7 subtypes of nAChRs were reported to be involved in such A␤-mediated interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The A␤ 1-42 -mediated increase in mEPSC frequency is antagonized by the nAChR antagonist dihydro-␤-erythroidine but not ␣-bungarotoxin Because A␤ 1-42 has been found to have high affinity to nAChRs and to be capable of influencing the function of these receptors (Wang et al, 2000a;Pettit et al, 2001;Fu and Jhamandas, 2003), we used dihydro-␤-erythroidine (DH␤E) (a selective ␣4␤2 nAChR antagonist) and ␣-bungarotoxin (a selective non-␣7 nAChR antagonist) to investigate the possible receptor subtypes involved in the A␤ 1-42 -mediated change in mEPSC frequency. We first tested the effect of DH␤E on the A␤ 1-42 -mediated increase in mEPSCs in identified cholinergic neurons.…”
Section: A␤ 1-42 Decreases Mepsc Frequency But Not Amplitude In Dbb Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Mecamylamine, at a concentration that inhibited nAChRs in cultured brain cells [7], and block nicotine's neuroprotective activity [12], did not affect cotinine neuroprotective activity. This evidence strongly suggests that cotinine triggers neuroprotective mechanisms distinctive from nicotine.…”
Section: Discussionmentioning
confidence: 92%
“…Pretreatment with mecamylamine (1 µM), a dose that inhibits nAChRs in cultured brain cells [7], did not affect the neuroprotective activity of cotinine and the increase in neuronal survival (p > 0.05) (Figure1B).…”
Section: Cotinine Is Neuroprotective Against Aβ Toxicitymentioning
confidence: 96%